Digital Mathematics Teaching Materials to Improve Student Learning Outcomes - Nurdiah Anggraeni Amir; Nurhikmah H; Farida Febriati (Universitas Pendidikan Ganesha, 2025)
Field observations reveal that teachers and students require flexible, independent, and interactive teaching materials that actively engage students in learning. Unlike conventional digital mathematics materials that are typically static, this study develops digital mathematics teaching materials that integrate sophisticated visual design through Canva with Heyzine's interactive flipbook technology to create immersive learning experiences. The product's primary innovation lies in seamless integration of mathematical content aligned with curriculum's Learning Objectives Flow (ATP), responsive visual design, and interactive flipbook features enabling intuitive navigation resembling physical book reading with comprehensive multimedia capabilities. This research encompasses five objectives: analyzing needs, designing, measuring validity, practicality, and effectiveness. The study employs R&D methodology using the ADDIE model. Research subjects comprised seventh-grade students. Findings demonstrate student needs analysis reached